National Romanticism: The Formation of National Movements - Balazs Trencsenyi, Michal Kopecek (Central European University Press, 2007)
This is the second of the four-volume series, a daring project of CEU Press, presenting the most important texts that triggered and shaped the processes of nation-building in the many countries of Central and Southeast Europe. 67 texts, including hymns, manifestos, articles or extracts from lengthy studies exemplify the relation between Romanticism and the national movements in the cultural space ranging from Poland to the Ottoman Empire. Each text is accompanied by a presentation of the auth...